Challenges and Critical Success Factors in Managing Virtual Teams: The Workplace of the Future - Nur Nazurah Zahar; Ismail, Fadillah; Umi Kartini Rashid (Advances in Humanities and Contemporary Studies, 2021)
The current working environment is constantly changing due to digitalization, automation, and individualization. The most recent industrial revolution, Industry 4.0 (4IR) has been introduced in several manufacturing industries globally which is characterized by the application of information and communication technologies. Many organizations responded to these changes by introducing virtual teams (VT) whose members are geographically dispersed, and their work is organized and communicated through ICT tools. This allows organizations to optimize teams by using only the best talent available. Therefore, this paper aims to identify contributing factors and barriers in managing a virtual team as well as examining its challenges. The COVID 19 pandemic even increased the need for modern literature to identify management challenges related to virtual team performance because organizations across the world suddenly have to work remotely from home, and an increasing number of employees now engage in full-time virtual teamwork